1973
DOI: 10.1063/1.1680477
|View full text |Cite
|
Sign up to set email alerts
|

Quenching cross sections for electronic energy transfer reactions between metastable argon atoms and noble gases and small molecules

Abstract: Reaction rate constants for the quenching of electronic energy in metastable argon (3P0,2) by Kr, Xe, and a number of simple molecules have been measured. A hollow, cold-cathode discharge excites the metastables in a flow apparatus. The concentration of metastables was followed by absorption spectroscopy as a function of time and of quenching molecule concentration. Quenching of Ar*(3P2) by Kr, CO, N2, CF4, and H2(D2) proceeds at rates between 0.6 and 7 × 10−11 cm3 molecule −1 · sec−1. Except for Kr, Xe, N2, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1
2

Year Published

1977
1977
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(71 citation statements)
references
References 56 publications
0
68
1
2
Order By: Relevance
“…However, the metastable states of argon, 3 P 0 and 3 P 2 , are efficiently quenched by H 2 , N 2 , N and H, see table 1, and the population of these states in the discharge is negligible [9][10][11][12].…”
Section: Production and Loss Of Excited Statesmentioning
confidence: 99%
“…However, the metastable states of argon, 3 P 0 and 3 P 2 , are efficiently quenched by H 2 , N 2 , N and H, see table 1, and the population of these states in the discharge is negligible [9][10][11][12].…”
Section: Production and Loss Of Excited Statesmentioning
confidence: 99%
“…For the quenching of the 3 P 0 and 3 P 2 states of Ar by CH 4 , the cross section values are 45 and 74 Å 2 , respectively. 6 Therefore, CH 4 ** states are efficiently populated via this mechanism and they attach low-energy electrons dissociatively producing H Ϫ and CH 3 , i.e., e Ϫ ϩCH 4 **→H Ϫ ϩCH 3 . It has been recently shown 7 that electron attachment to laser-excited superexcited states ͑electronically excited states lying above the ionization threshold͒ of CH 4 is extremely efficient.…”
mentioning
confidence: 99%
“…Thus, it can be concluded that very similar gas temperatures are achieved at lower RF powers by mixing N 2 with Ar. It is here mentioned that the Ar metastable atoms can excite the N 2 molecules [25] at low N 2 percentage (<1%) in Ar [33] producing an overpopulation of high rotational states of N 2 (C, v 0 ¼ 0). As such an overpopulation of rotational states has not been reported for the N 2 (B,v 0 ) states, it is here estimated that the rotational temperature of the N 2 (B,v 0 ¼ 2) state in Ar-20%N 2 gas mixtures is near the gas temperature.…”
Section: Rotational Temperaturesmentioning
confidence: 97%